Praktek Sewa Menyewa Meja Biliar - Diana Efrida Harahap; Ahmatnijar Ahmatnijar; Hasiah Hasiah (Jurnal El-Thawalib, 2021)
This research is entitled "The Practice of Renting Billiard Tables in Review From the Compilation of Sharia Economic Law (In Environment II Batunadua Jae)". The author is interested in conducting this research to obtain an overview of the practice of renting a billiard table in terms of sharia economic law. The purpose of this study is to find out the implementation of the practice of renting pool tables in Batunadua Jae Environment II, and to analyze from the point of view of sharia economic law about the practice of renting pool tables in Batunadua Jae Environment II. To get answers to research problems, the authors conduct research using field research methods using descriptive qualitative, where research is carried out in natural situations. The results of this study regarding the practice of renting a pool table can be said that someone knows how to play billiards mostly from friends and sees people playing billiards. How to play a billiard table in Batunadua Jae Ward II uses playing cards as a benchmark for the ball to be entered by players, besides that billiard players use money as bets or gambling. In the implementation of the billiard table rental in Lingkunagan II Batunadua Jae, it is contrary to the KHES contained in article 274 paragraph 2 which says that the object being liberated must be used for things that are justified according to sharia Because according to Islamic law it is not permissible to bet and gamble.